(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Changes that came with the new century were reflected in all societal areas. Neither individuals nor institutions were immune to societal transformations. One crucial aspect for the life of each person that undei*went significant transformations was the moral and value code. The new millennium brought new value hierarchy, new moral dilemmas, and new moral norms and caused certain type of moral panic in accordance with the transformations of moral. Today, humanity is still facing moral challenges of determining what is acceptable, preferable, right and good for the person and for the society. Value and moral code is not yet ideally balanced and harmonised with present societal needs and requirements. Young people, primarily student population, who are promoters of societal transformations and contemporary social discourse are standing in front of challenges and are directly involved in managing those challenges in individually and socially acceptable manner.